Pls give the answer of vii to me marked as brainliest and I will also follow for those who give me correct answer with steps and pls send it fast
Attachments:
![](https://hi-static.z-dn.net/files/d58/129548bf5cafc89fb74435cd981ba514.jpg)
Answers
Answered by
1
Given;
y - (13/2) = 6
It can be written as,
=> y = 6 + (13/2)
=> y = (6 * 2 + 13)/2
=> y = (12 + 13)/2
=> y = 25/2
Hope it help
Similar questions
Economy,
7 months ago
Physics,
7 months ago
English,
1 year ago
Social Sciences,
1 year ago
English,
1 year ago